1992
DOI: 10.1111/j.1600-0773.1992.tb00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Effects of α‐Adrenoceptor Blockade During Furosemide Diuresis in Conscious Rats

Abstract: Clearance experiments were performed in conscious rats in order to investigate whether intravenous infusion of the non-selective alpha-adrenoceptor antagonist phentolamine could block compensatory sodium reabsorption during furosemide-induced volume contraction. By measuring inulin clearance, urinary excretion rates of sodium and water, and lithium clearance, the effects on proximal and distal nephron segments were dissociated. The renal effect of intravenous infusion of 0.3 mg/kg/hr phentolamine (n = 6) was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The renal vasoconstrictor response and the decrease in GFR were unchanged in rats with AMX. The lack of effect of AMX on the decrease in RPF and GFR during volume depletion is in agreement with the lack of effect of SNX or phentolamine on the renal vasoconstriction and decrease in GFR that we have demonstrated during furosemide-induced volume depletion (IV; Petersen et al 1992). In accordance with the findings of Janssen et ul.…”
Section: Role Of the Adrenal Medulla In Arterial Blood Pressure Contrsupporting
confidence: 92%
See 2 more Smart Citations
“…The renal vasoconstrictor response and the decrease in GFR were unchanged in rats with AMX. The lack of effect of AMX on the decrease in RPF and GFR during volume depletion is in agreement with the lack of effect of SNX or phentolamine on the renal vasoconstriction and decrease in GFR that we have demonstrated during furosemide-induced volume depletion (IV; Petersen et al 1992). In accordance with the findings of Janssen et ul.…”
Section: Role Of the Adrenal Medulla In Arterial Blood Pressure Contrsupporting
confidence: 92%
“…Thus, increased plasma levels of vasoconstrictor substances and/or decreased plasma levels of hormones with vasodilator actions could mediate arteriolar vasoconstriction. This hypothesis is supported by numerous studies which have demonstrated increased plasma levels of norepinephrine, epinephrine, vasopressin, and angiotensin I1 during acute furosemide administration in both rat (DiPette & Rogers 1988;Petersen et al 1992), dog (Ueno et al 1980;Ueno et al 1983) and humans (Hesse et al 1975;Van Hooff et al 1983;Canella et al 1983;Kelly et al 1983;Francis et al 1985;Kubo et al 1987;Goldsmith et al 1989;Passmore et al 1989;Fujimura & Ebihara 1990;Okaniwa et al 1990;Jespersen et al 1991). The plasma concentration of the vasodilator hormone atrial natriuretic peptide decreases during furosemide diuresis, whereas furosemide produces an increase in both circulating and urinary excretion of prostaglandin E2 Dupont et al 1988;Fujimura & Ebihara 1990;Okaniwa et al 1990;Jespersen et al 1991).…”
Section: Effects Of Furosemide On Systemic and Renal Hemodynamicsmentioning
confidence: 66%
See 1 more Smart Citation
“…Thus, increasing the NHE3 activity probably via the traffic of the NHE3 protein between a cytoplasmic compartment and the apical membrane [62]may contribute to the short-term diuretic tolerance. However, neither the inhibition of angiotensin-converting enzyme nor adrenergic blockade, separately or together, consistently prevents it [63, 64, 65]. Thus, other as yet unidentified mechanisms must also be involved.…”
Section: Diuretic Tolerancementioning
confidence: 99%
“…Co administration of an angiotensin-converting enzyme inhibitor, however, appears to have no effect on braking [9][10][11], Similarly, it may be speculated that sympathoadrenal activa tion would increase proximal tubular reab sorption of sodium and contribute to the braking phenomenon. Studies in man with the cq-adrenoceptor antagonist prazosin have shown no effect on braking [11]; studies in animal models have both supported and re futed a role for the sympathetic nervous sys tem [12][13][14][15], Thus, although the braking sys tem is well characterized and is clearly a short-term modulator of response to loop di uretics, its mechanism is unclear. It is impor tant to emphasize that the trigger for the brak ing phenomenon is contraction of intravascu lar volume.…”
Section: Determinants Of Normal Responses To Loop Diureticsmentioning
confidence: 99%